Dispositional mindfulness and its relationship to exercise motivation and experience - Lynn, Sarah; Satyal, Medha Kumari; Smith, Alana J.; Tasnim, Noor; Gyamfi, Daphne; English, Daniel F.; Suzuki, Wendy A.; Basso, Julia C. (Frontiers in Sports and Active Living, 2022)
Mindfulness is the psychological state of staying attuned to the present moment, without ruminating on past or future events, and allowing thoughts, feelings, or sensations to arise without judgment or attachment. Previous work has shown that heightened dispositional mindfulness is associated with the awareness of the importance of exercise, exercise self-efficacy, exercise motivation, and self-reported exercise level. However, more methodologically rigorous studies are needed to understand the relationship between mindfulness and the psychological mechanisms related to exercise motivation, including the identification of why individuals are motivated to engage in exercise, the subjective experience of exercise, and the propensity for exercise dependence and addiction. In this cross-sectional investigation, we utilized the framework of the Self-Determination Theory to examine the hypothesis that heightened dispositional mindfulness (as measured by the Mindful Attention Awareness Scale) would be associated with increased levels of exercise motivation that were derived by higher levels of autonomous self-regulation. Individuals were recruited from urban areas who self-reported either low (exercising 2 or fewer times per week for 20 min or less; n = 78) or moderate (exercising 1 or 2 times per week for 20 min or more; n = 127) levels of exercise engagement. As hypothesized, heightened dispositional mindfulness was significantly associated with heightened levels of exercise self-determination as measured by the Behavioral Regulations in Exercise Questionnaire, with this effect being driven by negative associations with amotivation, external regulation, and introjected regulation. Additionally, we found that heightened dispositional mindfulness was associated with lower levels of psychological distress upon exercise and decreased exercise dependence/addiction. Overall, increased dispositional mindfulness may support a healthy relationship with exercise. These findings have implications for the utility of mindfulness interventions to support the regulation of exercise behaviors in service of enhancing exercise motivation and engagement.